How Czech Adolescents Perceive Their Physical Activity - Salonna, Ferdinand; Vorlíček, Michal; Rubín, Lukáš; Vašíčková, Jana; Mitáš, Josef (Children, 2023)
Adolescence is a critical stage in the development of an individual's physical activity (PA) habits and preferences. Adolescents' perceptions of PA can influence their motivation to engage in PA and, consequently, their overall level of PA. Thus, our primary aim was to investigate whether Czech adolescents misperceive their peers' PA. Our dataset comprised cross-sectional data on 1289 adolescents aged 11-15 years. PA was measured using self-reported items used in the HBSC study. To describe the gender and school grade differences in VPA, independent samples T, ANOVA, Mann-Whitney U, and Kruskal-Wallis H tests were performed. To analyze the effect of gender, school grade, school, and participants' own PA on the underestimation of PA, binomial regression models were used. Our study points out that there is a discrepancy between self-perceived levels of PA and the perceived descriptive norms of peers' PA. Adolescents underestimate the prevalence of sufficient PA, and thus perceived descriptive norms in PA as being worse than levels of own PA. These findings indicate room for targeted interventions based on social-norms-based approaches to increase the PA of adolescents or at least strengthen their actual positive behavior.